2022
DOI: 10.1021/acs.jpcb.2c02445
|View full text |Cite
|
Sign up to set email alerts
|

OH Stretching and Libration Bands of Solitary Water in Ionic Liquids and Dipolar Solvents Share a Single Dependence on Solvent Polarity

Abstract: Ionic liquids are an emerging class of materials which are finding application in a variety of technologically important areas. Because of their hydrophilic character, at least a small concentration of water is often present when ionic liquids are used in practical applications. This study employs infrared spectroscopy in the OH stretching and libration regions together with DFT calculations to better characterize the state of dilute water in ionic liquids. Water mole fractions (x w ∼ 0.1) are chosen such th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 89 publications
5
38
1
Order By: Relevance
“…We recently used mid-and farinfrared spectroscopy to better characterize the solvation and dynamics of dilute water in ionic liquids. 6 In that study, we found the OH-stretching spectra of isolated (monomeric) water to be more complex and indicative of a greater diversity of water solvation states than had been appreciated in prior investigations. Similar spectral features were also found in dipolar solvents of comparable polarity.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We recently used mid-and farinfrared spectroscopy to better characterize the solvation and dynamics of dilute water in ionic liquids. 6 In that study, we found the OH-stretching spectra of isolated (monomeric) water to be more complex and indicative of a greater diversity of water solvation states than had been appreciated in prior investigations. Similar spectral features were also found in dipolar solvents of comparable polarity.…”
Section: Introductionmentioning
confidence: 59%
“…The experimental spectra presented here are all taken from the compilation of data in Ref. 6. They are solvent-subtracted transmission spectra of 6-25 µm thick samples recorded at room temperature (21 ± 1) °C at 2 cm -1 resolution using a Bruker Vertex 70v spectrometer.…”
Section: A Experimentalmentioning
confidence: 99%
See 3 more Smart Citations